A High-throughput Microfluidic Rare Cell Enrichment System Based on Dielectrophoresis and Filtering. (2017) - Özkayar, Gürhan; Yalçın, Yağmur Demircan; Özgür, Ebru; Gündüz, Ufuk; Külah, Haluk
Abstract: In this study, a MEMS-based microfluidic device combining DEP-based cell manipulation with size-based filtration for the enrichment of CTCs from blood with high-throughput was developed. Positive-DEP (pDEP) force and the hydrodynamic force have been used to fine-tune the cell movement over the planar electrodes (sliding) at a high flow rate (30 μl/min). While smaller sized RBCs passed through the gaps and were directed to the waste channels, cancer cells (K562 cells) were filtered and directed to the cancer cell outlet. A cell enrichment factor and depletion rate of RBCs were calculated as 1.45 and 60%, respectively.